Analisis Kualitas Kinerja Sistem Smart Payment Dibisnis E-commerce - Prayoga Pidrosa; Rizki Pratama; Tata Sutabri (International Forum of Researchers and Lecturers, 2024)
The rapid development of e-commerce technology demands the adoption of efficient and reliable payment systems to enhance user experience. This research aims to analyze the quality of smart payment system performance in the context of e-commerce business. The analytical method used includes evaluating the reliability, responsiveness, transaction speed and security of the smart payment system. This study involved a survey of a number of e-commerce customers who use the smart payment system, with a focus on their perception of the quality of system performance. In addition, data collection is carried out by analyzing transaction times, failure rates and transaction security through smart payment systems used by several leading e-commerce platforms. The research results show that the reliability of the smart payment system has a significant impact on e-commerce user satisfaction. Additionally, responsiveness and transaction speed play an important role in ensuring optimal user experience. The security factor is also a critical aspect in increasing user trust in the smart payment system. This research provides valuable insights for e-commerce service providers and payment system developers to improve and optimize the performance quality of their smart payment systems. The implications of these findings can be used as a basis for developing better strategies in improving the efficiency and reliability of electronic payments in e-commerce businesses.